0555 Isolated REM Sleep Without Atonia Following COVID-19 Infection: A Case-Control Study. (25th May 2022) - Steele, Tyler; Bauer, David; Cesarone, Olivia; Lovold, Kevin; Paule, Gwen; Bibi, Noor; Strainis, Emma; Williams, Jacob; Jagielski, Jack; Feemster, John; Vissoneau, Laurene LeClair; Boeve, Bradley; et al.
Abstract: Introduction: REM sleep without atonia (RSWA) is the neurophysiological substrate of REM sleep behavior disorder (RBD), a form of prodromal parkinsonism in most older adults. Isolated RSWA (without clinical RBD) elevation was demonstrated recently in older adults following SARS-CoV2 (COVID-19) infection, but comparison to controls was not reported. We aimed to comparatively analyze RSWA between patients with previous COVID-19 infection and COVID-19 negative controls. Methods: 25 patients with previous COVID-19 infection were compared to 25 age-sex matched controls who tested negative for COVID-19 prior to polysomnography. Patients receiving medications known to increase RSWA were excluded. We reviewed medical records to determine clinical features and quantitatively analyzed RSWA in the submentalis (SM) and anterior tibialis (AT) muscles for phasic, tonic, and "any" muscle activity, phasic burst duration, and the automated REM atonia index. Non-parametric analyses compared clinical and polysomnographic features between groups, with combined SM and AT RSWA as the defined primary outcome. The comparative frequency of COVID-19 positive cases and COVID-19 negative controls who met or exceeded proposed isolated RSWA thresholds was also determined. Results: COVID-19 patients had significantly greater RSWA than COVID-19 negative controls in the combined SM and AT muscles (p = 0.00076). Most other RSWA metrics were also higher in COVID-19 patients than controls (p<0.03), except tonic muscle activity, phasic burst durations, and RAI. Isolated RSWA occurred more frequently in COVID-19 (9 patients, 36%) than controls (3, 12%; p>0.05). No patients had a clinical history or polysomnographic evidence for parasomnia behavior or a primary neurological condition. Conclusion: Quantitative RSWA amounts were comparatively greater in COVID-19 patients than in COVID-19 tested-negative controls, suggesting association of previous COVID-19 infection with central nervous system brainstem dysfunction in the region of the dorsal pons and/or ventromedial medulla. Further prospective studies are needed to determine whether RSWA is a predisposing influence to, or consequence of, COVID-19 infection in these patients, and whether COVID-19 survivors might harbor neurodegenerative risk or disease markers. Support (If Any):